Solar Cells
By using energy-level matching perovskite compounds and electron transport materials containing Ti and Zn in tin-based perovskite solar cells, the problem of low conversion efficiency in the prior art is solved and a higher conversion efficiency of solar cells is achieved.
Patent Information
- Application Number
- CN201910421830.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-05-25
- Filing Date
- 2019-05-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2039-05-21
AI Technical Summary
The existing tin perovskite solar cells have low conversion efficiency, mainly due to the mismatch between the energy level of the light absorption material and the bottom end of the conduction band of the electron transport material.
A perovskite compound represented by the chemical formula ASnX3 is used as the light absorption layer, and an electron transport material containing Ti and Zn is used in the electron transport layer to ensure that the difference between the bottom energy level of its conduction band and the bottom energy level of the perovskite compound is less than 0.42 eV.
By optimizing the energy level matching between light absorption materials and electron transport materials, the conversion efficiency of tin perovskite solar cells is significantly improved.
Smart Images

Figure CN110534649B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to solar cells. Background Art
[0002] In recent years, research and development of perovskite solar cells has been carried out. In perovskite solar cells, a perovskite compound represented by ABX3 (where A is a monovalent cation, B is a divalent cation, and X is a halogen anion) is used as a light absorbing material.
[0003] Non-patent document 1 discloses the use of a perovskite compound represented by the chemical formula CsSnI3 as a light absorbing material for a perovskite solar cell. In addition, non-patent document 1 discloses the use of TiO2 and an organic semiconductor called Spiro-OMETAD as an electron transport material and a hole transport material, respectively.
[0004] Non-patent document 2 discloses the use of a TiO2-ZnO-based ternary oxide as an electron transport material for a perovskite solar cell.
[0005] Prior Art Literature
[0006] Non-patent document 1: Mulmudi Hemant Kumar, 12 others, "Lead-free halideperovskite solar cells with high photocurrents realized through vacancy modulation", Advanced Materials, (UK), November 2014, Vol. 26, No. 41, p. 7122-7127
[0007] Non-patent document 2: Xiong Yin, 4 others, “Ternary Oxides in the TiO2-ZnO Systems as Efficient Electron-Transport Layers for Perovskite Solar Cells with Efficiency over 15%”, Applied Materials and Interfaces, October 2016, 8(43), p.29580-29587 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The purpose of the present disclosure is to provide a tin-based perovskite solar cell with further improved conversion efficiency.
[0010] Means for solving problems
[0011] The solar cell according to the present disclosure comprises a first electrode, a second electrode, a light absorbing layer located between the first electrode and the second electrode, and an electron transport layer located between the first electrode and the light absorbing layer, wherein:
[0012] At least one electrode selected from the first electrode and the second electrode has light-transmitting property,
[0013] The light absorbing layer contains a perovskite compound represented by the chemical formula ASnX3 (wherein A is a monovalent cation and X is a halogen anion),
[0014] The electron transport layer contains an electron transport material containing Ti and Zn, and
[0015] The difference between the conduction band bottom energy level of the electron transport material and the conduction band bottom energy level of the perovskite compound is less than 0.42 eV.
[0016] Effects of the Invention
[0017] The present disclosure provides a tin-based perovskite solar cell with further improved conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A cross-sectional view showing a solar cell according to an embodiment of the present disclosure.
[0019] Figure 2 A cross-sectional view showing a solar cell according to a modified example of the embodiment of the present disclosure.
[0020] Figure 3 is the chemical formula Ti representing the electron transport material contained in the solar cells of the examples and comparative examples. x Zn 1- x O 1+x A graph showing the relationship between the value of x in and the bottom energy level of the conduction band of the electron transport material.
[0021] Figure 4 is the chemical formula Ti representing the electron transport material contained in the solar cells of the examples and comparative examples. x Zn 1- x O 1+x A graph showing the relationship between the value of x in , the conduction band bottom energy level of the electron transport material, and the conversion efficiency of the solar cell. DETAILED DESCRIPTION
[0022] (Definition of terms)
[0023] The term "perovskite compound" used in this specification refers to a perovskite crystal structure represented by the chemical formula ABX3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) and a crystal structure similar thereto.
[0024] The term "tin-based perovskite compound" used in this specification refers to a perovskite compound containing tin.
[0025] The term "tin-based perovskite solar cell" used in this specification refers to a solar cell including a tin-based perovskite compound as a light-absorbing material.
[0026] <Foundation that forms the basis of this disclosure>
[0027] The findings leading to the present disclosure will be described below.
[0028] Tin-based perovskite compounds have excellent physical properties as light-absorbing materials, so it is expected that tin-based perovskite solar cells have high conversion efficiency. In order to further improve the conversion efficiency of tin-based perovskite solar cells, the inventors focus on the matching between the bottom energy level of the conduction band of the light-absorbing material and the bottom energy level of the conduction band of the electron transport material. Hereinafter, the bottom energy level of the conduction band is referred to as the "conduction band energy level".
[0029] As disclosed in non-patent document 1, in previous tin-based perovskite solar cells, the electron transport material is usually TiO2. TiO2 is suitable for matching the conduction band energy level with respect to lead-containing perovskite compounds (hereinafter referred to as "lead-based perovskite compounds"). However, TiO2 is not suitable for matching the conduction band energy level with respect to tin-based perovskite compounds. Specifically, the conduction band energy level of tin-based perovskite compounds is about 0.5eV to 0.6eV shallower than the conduction band energy level of lead-based perovskite compounds. Therefore, TiO2 is a suitable electron transport material for lead-based perovskite solar cells, but it is not a suitable electron transport material for tin-based perovskite compounds. This is because the conduction band energy level of TiO2 is too deep relative to tin-based perovskite compounds.
[0030] The present disclosure provides a solar cell using an electron transport material having a suitable conduction band energy level with respect to a tin-based perovskite compound. The solar cell has a higher conversion efficiency than a conventional tin-based perovskite solar cell.
[0031] <Embodiments of the present disclosure>
[0032] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings.
[0033] Figure 1 1 is a cross-sectional view of a solar cell 100 according to this embodiment. Figure 1As shown, the solar cell 100 involved in this embodiment includes a first electrode 2, a second electrode 6, a light absorbing layer 4 and an electron transport layer 3. The light absorbing layer 4 is located between the first electrode 2 and the second electrode 6. The electron transport layer 3 is located between the first electrode 2 and the light absorbing layer 4. The first electrode 2 is opposite to the second electrode 6, and the electron transport layer 3 and the light absorbing layer 4 are arranged between the first electrode 2 and the second electrode 6. At least one electrode selected from the first electrode 2 and the second electrode 6 is light-transmitting. In this specification, "the electrode is light-transmitting" means that more than 10% of light with a wavelength of more than 200nm and less than 2000nm is transmitted through the electrode at any wavelength.
[0034] The light absorbing layer 4 contains a perovskite compound represented by the chemical formula ASnX3 (wherein A is a monovalent cation and X is a halogen anion) as a light absorbing material. There is no limitation on the monovalent cation located at the A site. Examples of monovalent cations include organic cations or alkali metal cations. Examples of organic cations include methylammonium cations (i.e., CH3NH3 + ), formamidinium cation (i.e., NH2CHNH2 + ), phenethylammonium cation (ie, C6H5CH2CH2NH3 + ) or guanidinium cation (ie, CH6N3 + Examples of alkali metal cations include cesium cations (Cs + ). The monovalent cation at the A site is preferably a carboxamidinium cation. The monovalent cation at the A site may also be composed of two or more cations. An example of a halogen anion at the X site is an iodide ion. The halogen anion at the X site may be composed of two or more halogen ions.
[0035] The light absorbing layer 4 may contain materials other than the light absorbing material. For example, the light absorbing layer 4 may further contain a quenching substance for reducing the defect density of the perovskite compound represented by the chemical formula ASnX3. Examples of the quenching substance include fluorine compounds such as tin fluoride.
[0036] The electron transport layer 3 contains an electron transport material containing Ti and Zn. The electron transport material containing Ti and Zn is suitable in terms of matching the conduction band energy level of the perovskite compound represented by the chemical formula ASnX3. Specifically, the difference between the conduction band bottom energy level of the electron transport material containing Ti and Zn and the conduction band bottom energy level of the perovskite compound represented by the chemical formula ASnX3 is a small value less than 0.42eV. The difference can be less than 0.23eV, less than 0.09eV, or less than 0.01eV.
[0037] The conduction band bottom energy level of the electron transport material containing Ti and Zn may be greater than -3.89 eV and less than -3.05 eV, or may be greater than -3.46 eV and less than -3.24 eV, based on the vacuum level.
[0038] The electron transport material containing Ti and Zn may be a material having the chemical formula Ti x Zn 1-x O 1+x (where 0<x<1). In this chemical formula, the value of x may be 0.20 or more and 0.73 or less.
[0039] The electron transport layer 3 may or may not be in contact with the light absorbing layer 4. When the electron transport layer 3 is in contact with the light absorbing layer 4, the electron transport material containing Ti and Zn may be provided on the surface of the electron transport layer 3 in contact with the light absorbing layer 4. The electron transport layer 3 may contain a plurality of electron transport materials. The electron transport layer 3 may be composed of a plurality of layers formed by electron transport materials different from each other. When the electron transport layer 3 is composed of a plurality of layers, for example, the layer in contact with the light absorbing layer 4 contains an electron transport material containing Ti and Zn.
[0040] Figure 1 In the solar cell 100 shown, a first electrode 2, an electron transport layer 3, a light absorption layer 4, a hole transport layer 5, and a second electrode 6 are sequentially stacked on a substrate 1. The solar cell 100 may not have the substrate 1. The solar cell 100 may not have the hole transport layer 5.
[0041] Next, the basic effects of the solar cell 100 are described. When the solar cell 100 is irradiated with light, the light absorbing layer 4 absorbs the light and generates excited electrons and holes. The excited electrons move to the electron transport layer 3. On the other hand, the holes generated in the light absorbing layer 4 move to the hole transport layer 5. The electron transport layer 3 and the hole transport layer 5 are electrically connected to the first electrode 2 and the second electrode 6, respectively. Current is taken out from the first electrode 2 and the second electrode 6, which function as a negative electrode and a positive electrode, respectively.
[0042] The solar cell 100 is produced, for example, by the following method.
[0043] First, the first electrode 2 is formed on the surface of the substrate 1 by chemical vapor deposition (CVD) or sputtering.
[0044] Next, an electron transport layer 3 is formed on the first electrode 2 by a coating method such as a spin coating method or a sputtering method. The electron transport layer 3 contains an electron transport material containing Ti and Zn. When the electron transport layer 3 is formed by a spin coating method, a Ti raw material and a Zn raw material are dissolved in a solvent in a predetermined ratio to obtain a solution, and the solution is applied to the first electrode 2 by a spin coating method. In this way, a coating film is formed. The coating film is sintered in air at a predetermined temperature (for example, above 300°C and below 500°C). Examples of Ti raw materials include tetraisopropyl titanate or TiCl4. Examples of Zn raw materials include ZnCl2 or zinc acetate. Examples of solvents include isopropyl alcohol or ethanol.
[0045] The light absorbing layer 4 is formed on the electron transport layer 3. The light absorbing layer 4 can be formed by the following method. As an example, the following method is used to form a light absorbing layer having a chemical formula (HC(NH2)2): 1-y (C6H5CH2CH2NH3) y SnI3 (where 0<y<1, hereinafter referred to as “FA 1- y PEA y A method for forming the light absorbing layer 4 of a perovskite compound represented by SnI3”) is described.
[0046] First, SnI2, HC(NH2)2I (hereinafter referred to as "FAI") and C6H5CH2CH2NH3I (hereinafter referred to as "PEAI") are added to an organic solvent to obtain a mixed solution. An example of an organic solvent is a mixed solution of dimethyl sulfoxide (hereinafter referred to as "DMSO") and N,N-dimethylformamide (hereinafter referred to as "DMF") (DMSO:DMF=1:1 (volume ratio)). The molar concentration of SnI2 can be greater than 0.8 mol / L and less than 2.0 mol / L, or greater than 0.8 mol / L and less than 1.5 mol / L. The molar concentration of FAI can be greater than 0.8 mol / L and less than 2.0 mol / L, or greater than 0.8 mol / L and less than 1.5 mol / L. The molar concentration of PEAI can be greater than 0.1 mol / L and less than 0.3 mol / L, or greater than 0.1 mol / L and less than 0.5 mol / L.
[0047] Next, the mixed solution was heated to a temperature of 40° C. or higher and 180° C. or lower using a heating device. Thus, a mixed solution in which SnI 2 , FAI, and PEAI were dissolved was obtained. Then, the obtained mixed solution was left at room temperature.
[0048] The mixed solution is applied to the electron transport layer 3 by spin coating, and then heated at a temperature of 40° C. to 100° C. for 15 minutes to 1 hour. Thus, the light absorbing layer 4 is obtained. When the mixed solution is applied by spin coating, a poor solvent may be added dropwise during the spin coating process. Examples of the poor solvent include toluene, chlorobenzene, or diethyl ether.
[0049] The mixed solution may contain a quenching substance such as tin fluoride. The concentration of the quenching substance may be 0.05 mol / L or more and 0.4 mol / L or less. The quenching substance suppresses the generation of defects in the light absorbing layer 4, that is, suppresses the generation of Sn holes. 4+ The increase of promotes the generation of Sn holes.
[0050] A hole transport layer 5 is formed on the light absorbing layer 4. Examples of methods for forming the hole transport layer 5 include coating or printing. Examples of coating methods include blade coating, rod coating, spray coating, dip coating, or spin coating. Examples of printing methods include screen printing. The hole transport layer 5 may be formed by mixing a plurality of materials, and then the hole transport layer 5 may be pressurized or fired. In the case where the hole transport layer 5 is formed of an organic low molecular weight substance or an inorganic semiconductor, the hole transport layer 5 may be formed by vacuum evaporation.
[0051] Next, the second electrode 6 is formed on the hole transport layer 5. In this way, the solar cell 100 is obtained. The second electrode 6 can be formed by a CVD method or a sputtering method.
[0052] Hereinafter, the elements of the solar cell 100 will be described in more detail.
[0053] (Substrate 1)
[0054] The substrate 1 is used to hold the first electrode 2, the electron transport layer 3, the light absorption layer 4, and the second electrode 6. The substrate 1 can be formed of a transparent material. Examples of the substrate 1 include a glass substrate or a plastic substrate. Examples of the plastic substrate include a plastic film. In the case where the first electrode 2 has sufficient strength, since the first electrode 2 holds the electron transport layer 3, the light absorption layer 4, and the second electrode 6, the solar cell 100 may not have the substrate 1.
[0055] (First electrode 2 and second electrode 6)
[0056] The first electrode 2 and the second electrode 6 are conductive. At least one of the first electrode 2 and the second electrode 6 is light-transmissive. The light-transmissive electrode can transmit light from the visible light region to the near-infrared region, for example. The light-transmissive electrode can be formed of at least one of a metal oxide and a metal nitride that is transparent and conductive.
[0057] Examples of metal oxides are
[0058] (i) titanium oxide doped with at least one selected from lithium, magnesium, niobium and fluorine,
[0059] (ii) gallium oxide doped with at least one selected from tin and silicon,
[0060] (iii) indium-tin composite oxide,
[0061] (iv) tin oxide doped with at least one selected from antimony and fluorine,
[0062] (v) Zinc oxide doped with at least one selected from boron, aluminum, gallium and indium.
[0063] A composite composed of two or more metal oxides may also be used.
[0064] An example of the metal nitride is gallium nitride doped with at least one selected from silicon and oxygen. Two or more metal nitrides may be used in combination.
[0065] Metal oxides and metal nitrides may be used in combination.
[0066] The first electrode 2 can be formed by using an opaque material and providing a light-transmitting pattern. As the pattern to be transmitted, for example, a linear, wavy, lattice-shaped, and a punched metal-like pattern formed by regular or irregular arrangement of a plurality of fine through holes can be cited. If the first electrode 2 has these patterns, light can be transmitted through the portion where the electrode material is not present. As the opaque material, for example, platinum, gold, silver, copper, aluminum, rhodium, indium, titanium, iron, nickel, tin, zinc, and an alloy containing any of these metals can be cited. In addition, a conductive carbon material can also be used.
[0067] The solar cell 100 includes the electron transport layer 3 between the light absorbing layer 4 and the first electrode 2. Therefore, the first electrode 2 does not need to block holes moving from the light absorbing layer 4. Therefore, the first electrode 2 can be formed of a material capable of forming an ohmic contact with the light absorbing layer 4.
[0068] In the case where the solar cell 100 does not have a hole transport layer 5, the second electrode 6 is formed of a material having an electron blocking property that blocks electrons moving from the light absorbing layer 4. In this case, the second electrode 6 is not in ohmic contact with the light absorbing layer 4. The electron blocking property that blocks electrons moving from the light absorbing layer 4 means that only holes generated in the light absorbing layer 4 are allowed to pass through, and electrons are not allowed to pass through. The Fermi level of the material having an electron blocking property is lower than the bottom end energy level of the conduction band of the light absorbing layer 4. The Fermi level of the material having an electron blocking property may be lower than the Fermi level of the light absorbing layer 4. Specifically, the second electrode 6 may be formed of a carbon material such as platinum, gold, or graphene. These materials have electron blocking properties, but do not have light transmittance. Therefore, in the case of forming the light-transmitting second electrode 6 using such a material, as described above, the second electrode 6 having a light-transmitting pattern is formed. In the case where the solar cell 100 has a hole transport layer 5 between the light absorbing layer 4 and the second electrode 6, the second electrode 6 may not have an electron blocking property that blocks electrons moving from the light absorbing layer 4. Therefore, the second electrode 6 can be formed of a material that can come into ohmic contact with the light absorbing layer 4 .
[0069] The light transmittance of the first electrode 2 and the second electrode 6 may be 50% or more, or 80% or more. The wavelength of light transmitted through the electrodes depends on the absorption wavelength of the light absorbing layer 4. The thickness of each of the first electrode 2 and the second electrode 6 is, for example, 1 nm or more and 1000 nm or less.
[0070] (Electron transport layer 3)
[0071] As described above, the electron transport layer 3 contains the electron transport material containing Ti and Zn.
[0072] The electron transport layer 3 may contain an electron transport material other than the electron transport material containing Ti and Zn. In this case, the electron transport layer 3 may be composed of a plurality of layers formed by different electron transport materials. In the case where the electron transport layer 3 is composed of a plurality of layers, for example, the layer in contact with the light absorbing layer 4 may contain an electron transport material containing Ti and Zn.
[0073] The electron transport material other than the electron transport material containing Ti and Zn may be a material known as an electron transport material for a solar cell. The known material may be a semiconductor having a band gap of 3.0 eV or more. In the case where the electron transport layer 3 includes a semiconductor having a band gap of 3.0 eV or more, visible light and infrared light reach the light absorbing layer 4. Examples of the semiconductor include organic or inorganic n-type semiconductors.
[0074] Examples of organic n-type semiconductors include imide compounds, quinone compounds, fullerenes or fullerene derivatives. Examples of inorganic n-type semiconductors include metal oxides, metal nitrides or perovskite oxides. Examples of metal oxides include oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si or Cr. TiO2 is preferred. Examples of metal nitrides include GaN. Examples of perovskite oxides include SrTiO3 or CaTiO3.
[0075] The electron transport layer 3 may contain a substance having a band gap greater than 6.0 eV. Examples of substances having a band gap greater than 6.0 eV include (i) alkali metal halides or alkaline earth metal halides such as lithium fluoride or calcium fluoride, (ii) alkaline earth metal oxides such as magnesium oxide, or (iii) silicon dioxide. In this case, in order to ensure the electron transport property of the electron transport layer 3, the thickness of the electron transport layer 3 is, for example, less than 10 nm.
[0076] (Light absorbing layer 4)
[0077] The light absorbing layer 4 contains a perovskite compound represented by the chemical formula ASnX3 as described above. The light absorbing layer 4 may mainly contain a perovskite compound represented by the chemical formula ASnX3. "The light absorbing layer 4 mainly contains a perovskite compound represented by the chemical formula ASnX3" means that the light absorbing layer 4 contains 70% by mass or more of the perovskite compound represented by the chemical formula ASnX3. The light absorbing layer 4 may contain 80% by mass or more of the perovskite compound. The light absorbing layer 4 may also contain compounds other than the perovskite compound represented by the chemical formula ASnX3. The light absorbing layer 4 may contain impurities.
[0078] The thickness of the light absorbing layer 4 is, for example, 100 nm to 10 μm. The thickness of the light absorbing layer 4 may be 100 nm to 1000 nm. The thickness of the light absorbing layer 4 depends on the light absorption of the light absorbing layer 4. The light absorbing layer 4 can be formed by a coating method using a solution.
[0079] (Hole Transport Layer 5)
[0080] The hole transport layer 5 is composed of an organic substance or an inorganic semiconductor. Representative examples of organic substances used for the hole transport layer 5 include 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)9,9'-spirobifluorene (hereinafter referred to as "spiro-OMeTAD"), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (hereinafter referred to as "PTAA"), poly(3-hexylthiophene-2,5-diyl) (hereinafter referred to as "P3HT") or poly(3,4-ethylenedioxythiophene) (hereinafter referred to as "PEDOT"), and copper phthalocyanine (hereinafter referred to as "CuPC").
[0081] Examples of inorganic semiconductors are Cu2O, CuGaO2, CuSCN, CuI, NiO x 、MoO x , V2O5 or carbon materials such as graphene oxide.
[0082] The hole transport layer 5 may include a plurality of layers formed of materials different from each other.
[0083] The thickness of the hole transport layer 5 may be greater than 1 nm and less than 1000 nm, may be greater than 10 nm and less than 500 nm, or may be greater than 10 nm and less than 50 nm. If the thickness of the hole transport layer 5 is greater than 1 nm and less than 1000 nm, sufficient hole transport properties can be exhibited. In addition, if the thickness of the hole transport layer 5 is greater than 1 nm and less than 1000 nm, since the resistance of the hole transport layer 5 is low, light can be converted into electricity with high efficiency.
[0084] The hole transport layer 5 may contain a supporting electrolyte and a solvent. The supporting electrolyte and the solvent stabilize the holes in the hole transport layer 5.
[0085] Examples of supporting electrolytes include ammonium salts or alkali metal salts. Examples of ammonium salts include tetrabutylammonium perchlorate, tetraethylammonium hexafluorophosphate, imidazole Salt or pyridine Examples of the alkali metal salt are lithium bis(trifluoromethanesulfonyl)imide (hereinafter referred to as "LiTFSI"), LiPF6, LiBF4, lithium perchlorate or potassium tetrafluoroborate.
[0086] The solvent contained in the hole transport layer 5 may have high ion conductivity. The solvent may be an aqueous solvent or an organic solvent. From the viewpoint of stabilization of the solute, an organic solvent is preferred. Examples of organic solvents include heterocyclic compounds such as tert-butylpyridine, pyridine, or N-methylpyrrolidone.
[0087] The solvent contained in the hole transport layer 5 may be an ionic liquid. The ionic liquid may be used alone or in a mixture with other solvents. The ionic liquid is preferred in terms of low volatility and high flame retardancy.
[0088] Examples of ionic liquids are 1-ethyl-3-methylimidazole Imidazoles such as tetracyanoborates Compounds, pyridine compounds, alicyclic amine compounds, aliphatic amine compounds or nitrogen Amine compounds.
[0089] Figure 2 A cross-sectional view showing a modified example of the solar cell 200 according to the present embodiment. Figure 1 Unlike the solar cell 100 shown, the solar cell 200 includes a porous layer 7 .
[0090] Figure 2 In the solar cell 200 shown, a first electrode 2, a porous layer 7, an electron transport layer 3, a light absorption layer 4, a hole transport layer 5, and a second electrode 6 are sequentially stacked on a substrate 1. The porous layer 7 includes a porous body. The porous body includes pores. The solar cell 200 may not have the substrate 1. The solar cell 200 may not have the hole transport layer 5.
[0091] The pores included in the porous layer 7 are connected from the portion in contact with the first electrode 2 to the portion in contact with the electron transport layer 3. The pores included in the porous layer 7 are filled with the material of the electron transport layer 3. Since the first electrode 2 is in contact with the electron transport layer 3, electrons move directly from the electron transport layer 3 to the first electrode 2.
[0092] Next, the basic effects of the solar cell 200 are described. When the solar cell 200 is irradiated with light, the light absorbing layer 4 absorbs the light and generates excited electrons and holes. The excited electrons move to the electron transport layer 3. On the other hand, the holes generated in the light absorbing layer 4 move to the hole transport layer 5. As described above, the electron transport layer 3 and the hole transport layer 5 are electrically connected to the first electrode 2 and the second electrode 6, respectively, so that current is taken out from the first electrode 2 and the second electrode 6, which function as the negative electrode and the positive electrode, respectively.
[0093] The porous layer 7 facilitates the formation of the light absorbing layer 4. The electron transport layer 3 formed on the porous layer 7 will cover the surface and pore walls of the porous layer 7. Since the thickness of the electron transport layer 3 is small, the shape of the surface and pores of the porous layer 7 is maintained. In this case, the material of the light absorbing layer 4 will also invade the inside of the pores of the porous layer 7 covered by the electron transport layer 3. Therefore, the possibility of the material of the light absorbing layer 4 being repelled or agglomerated on the surface of the electron transport layer 3 is reduced. Therefore, the porous layer 7 becomes a support for the light absorbing layer 4, and the light absorbing layer 4 can be formed into a uniform film. The light absorbing layer 4 can be formed by applying a solution on the electron transport layer 3 by spin coating and heating it.
[0094] Light is scattered by the porous layer 7. Therefore, the optical path length of light passing through the light absorbing layer 4 increases. The increase in the optical path length can increase the amount of electrons and holes generated in the light absorbing layer 4.
[0095] The solar cell 200 can be produced by the same method as the solar cell 100. The porous layer 7 is formed on the first electrode 2 by, for example, a coating method.
[0096] (Porous layer 7)
[0097] The porous layer 7 serves as a support for forming the light absorbing layer 4. The porous layer 7 does not hinder the movement of electrons from the light absorbing layer 4 to the first electrode 2.
[0098] The porous layer 7 includes a porous body. Examples of porous bodies include porous bodies formed by connecting insulating or semiconductor particles. Examples of insulating particles include aluminum oxide or silicon oxide. Examples of semiconductor particles include inorganic semiconductor particles. Examples of inorganic semiconductors include metal oxides (including perovskite oxides), metal sulfides or metal chalcogenides. Examples of metal oxides include oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si or Cr. TiO2 is preferred. Examples of perovskite oxides include SrTiO3 or CaTiO3. Examples of metal sulfides include CdS, ZnS, In2S3, SnS, PbS, Mo2S, WS2, Sb2S3, Bi2S3, ZnCdS2 or Cu2S. Examples of metal chalcogenides are CdSe, CsSe, In2Se3, WSe2, HgS, SnSe, PbSe or CdTe.
[0099] The thickness of the porous layer 7 can be greater than 0.01 μm and less than 10 μm, or greater than 0.1 μm and less than 1 μm. The porous layer 7 can have a large surface roughness. Specifically, the surface roughness coefficient calculated by effective area / projected area can be greater than 10, or greater than 100. Furthermore, the projected area refers to the area of the shadow formed at the rear when light is irradiated to the object from the front. The effective area refers to the actual surface area of the object. The effective area can be calculated based on the volume calculated from the projected area and thickness of the object, and the specific surface area and bulk density of the material constituting the object. The specific surface area is measured, for example, by nitrogen adsorption.
[0100] (Example)
[0101] The present disclosure is described in more detail with reference to the following examples.
[0102] [Example 1]
[0103] In Example 1, the following preparation was performed Figure 2 A tin-based perovskite solar cell 200 is shown.
[0104] A glass substrate having an indium-doped SnO2 layer on its surface was prepared. The glass substrate was a product of Nippon Sheet Glass Co., Ltd. The glass substrate and the SnO2 layer functioned as a substrate 1 and a first electrode 2, respectively. The thickness of the glass substrate was 1 mm.
[0105] A high-purity titanium oxide powder having an average primary particle size of 30 nm was dispersed in ethyl cellulose to prepare a titanium oxide paste.
[0106] The prepared titanium oxide paste was applied onto the first electrode 2 by screen printing and then dried. The titanium oxide paste was fired in air at 500° C. for 30 minutes to form a porous layer 7 consisting of a porous titanium oxide layer with a thickness of 0.2 μm.
[0107] Next, an isopropanol solution containing tetraisopropyl titanate (hereinafter referred to as "TTIT") and ZnCl2 was prepared. The isopropanol solution had a TTIT concentration of 10.6 mmol / L and a ZnCl2 concentration of 3.9 mmol / L. The isopropanol solution (80 μl) was applied to the porous layer 7 by spin coating, and then sintered at 350°C in air for 1 hour. 0.73 Zn 0.27 O 1.73 The electron transport layer 3 is formed. The film thickness of the electron transport layer 3 is about 10 nm. The composition of the electron transport material of the electron transport layer 3 is Ti 0.73 Zn 0.27 O 1.73 , depending on the ratio of Zn to Ti contained in the isopropyl alcohol solution. The composition of the electron transport material of the electron transport layer 3 can be determined based on the result of X-ray photoelectron spectroscopy of the electron transport layer 3 .
[0108] Then, SnI2, SnF2, FAI (i.e., HC(NH2)2I) and PEAI (i.e., C6H5CH2CH2NH3I) were added to a mixed solvent of DMSO and DMF to obtain a mixed solution. The volume ratio of DMSO:DMF in the mixed solvent was 1:1. The concentrations of SnI2, SnF2, FAI and PEAI in the mixed solution were 1.5 mol / L, 0.15 mol / L, 1.5 mol / L and 0.3 mol / L, respectively.
[0109] In the glove box, the mixed solution (80 μL) was applied to the electron transport layer 3 by spin coating to obtain a coating film with a thickness of 500 nm. Then, the coating film was fired on a hot plate at 80°C to form a light absorbing layer 4. The light absorbing layer 4 mainly contained a chemical formula of FA 0.83 PEA 0.17Perovskite compound of SnI3. The chemical formula is FA 0.83 PEA 0.17 The conduction band bottom energy level of the SnI3 perovskite compound is -3.47 eV based on the vacuum level. The conduction band bottom energy level of the perovskite compound is measured in the same manner as the conduction band bottom energy level of the electron transport material. The measurement method will be described later.
[0110] Next, in a glove box, a toluene solution (80 μl) containing PTAA (i.e., poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) at a concentration of 10 mg / ml was applied onto the light absorbing layer 4 by spin coating to form a hole transport layer 5 with a thickness of 10 nm.
[0111] Finally, a gold film with a thickness of 100 nm was deposited on the hole transport layer 5 to form the second electrode 6. In this way, the tin-based perovskite solar cell of Example 1 was obtained.
[0112] [Example 2]
[0113] In Example 2, a tin-based perovskite solar cell 200 was obtained in the same manner as in Example 1 except for the following matter (i).
[0114] (i) The concentrations of TTIT and ZnCl2 contained in the isopropanol solution are 6.5 mmol / L and 8.0 mmol / L, respectively.
[0115] In Example 2, the electron transport layer 3 is made of Ti 0.45 Zn 0.55 O 1.45 The electron transport material of the electron transport layer 3 is composed of Ti 0.45 Zn 0.55 O 1.45 It is determined based on the ratio of Ti to Zn contained in the isopropanol solution.
[0116] [Example 3]
[0117] In Example 3, a tin-based perovskite solar cell 200 was obtained in the same manner as in Example 1 except for the following matter (i).
[0118] (i) The concentrations of TTIT and ZnCl2 contained in the isopropanol solution are 3.0 mmol / L and 11.5 mmol / L, respectively.
[0119] In Example 3, the electron transport layer 3 is made of Ti 0.21 Zn 0.79 O 1.21 The electron transport material of the electron transport layer 3 is composed of Ti 0.21 Zn 0.79 O 1.21It is determined based on the ratio of Ti to Zn contained in the isopropanol solution.
[0120] [Comparative Example 1]
[0121] In Comparative Example 1, a tin-based perovskite solar cell 200 was obtained in the same manner as in Example 1 except for the following item (i).
[0122] (i) The concentrations of TTIT and ZnCl2 contained in the isopropyl alcohol solution were 14.5 mmol / L and 0 mmol / L, respectively. That is, in Comparative Example 1, ZnCl2 was not used.
[0123] In Comparative Example 1, the electron transport layer 3 is formed of TiO 2 .
[0124] [Comparative Example 2]
[0125] In Comparative Example 2, a tin-based perovskite solar cell 200 was obtained in the same manner as in Example 1 except for the following matter (i).
[0126] (i) The concentrations of TTIT and ZnCl2 contained in the isopropyl alcohol solution were 0 mmol / L and 14.5 mmol / L, respectively. That is, in Comparative Example 2, TTIT was not used.
[0127] In Comparative Example 2, the electron transport layer 3 is formed of ZnO.
[0128] [Method for determining the bottom energy level of the conduction band of electron transport materials]
[0129] The bottom energy level of the conduction band of the electron transport material of the electron transport layer 3 is calculated based on ultraviolet electron spectroscopy and transmittance measurement. Specifically, a laminate of the substrate 1, the first electrode 2, and the electron transport layer 3 is used as a measurement sample. The measurement sample does not have a light absorption layer 4, a hole transport layer 5, and a second electrode 6. In other words, the measurement sample has an electron transport layer 3 on the surface.
[0130] The sample for measurement was subjected to ultraviolet electron spectrometry using an ultraviolet electron spectrometer (manufactured by ULVAC-PHI Co., Ltd., trade name: PHI 5000 Versa Probe), and the valence band upper end energy level of the electron transport material was calculated.
[0131] The sample for measurement was subjected to transmittance measurement using a transmittance measuring apparatus (SlidSpec-3700 manufactured by Shimadzu Corporation). Based on the result of the transmittance measurement, the band gap of the electron transport material was calculated.
[0132] Based on these calculated valence band upper energy levels and band gaps, the conduction band bottom energy levels of the electron transport material are calculated.
[0133] Figure 3The chemical formula representing the electron transport material is Ti x Zn 1-x O 1+x The relationship between the value of x contained in and the bottom energy level of the conduction band of the electron transport material.
[0134] [Conversion efficiency]
[0135] The tin-based perovskite solar cells 200 of Examples 1 to 3 and Comparative Examples 1 to 2 were irradiated with a solar energy of 100 mW / cm 2 The conversion efficiency of each tin-based perovskite solar cell 200 was calculated using simulated sunlight with an illumination of . Table 1 shows the calculation results. Figure 4 is the chemical formula Ti representing the electron transport material x Zn 1-x O 1+x A graph showing the relationship between the value of x contained in , the conduction band bottom energy level of the electron transport material, and the conversion efficiency of the solar cell.
[0136] Table 1
[0137]
[0138] As shown in Table 1 and Figure 4 As shown, in the tin-based perovskite solar cells 200 of Examples 1 to 3, the difference between the bottom energy level of the conduction band of the electron transport material of the electron transport layer 3 and the bottom energy level of the conduction band of the perovskite compound contained in the light absorption layer 4 (i.e., -3.47 eV) is less than 0.42 eV. On the other hand, in the tin-based perovskite solar cells 200 of Comparative Examples 1 to 2, the difference is greater than 0.42 eV. The tin-based perovskite solar cells 200 of Examples 1 to 3 have higher conversion efficiency than the tin-based perovskite solar cells 200 of Comparative Examples 1 to 2.
[0139] Industrial Availability
[0140] The solar cell of the present disclosure is installed on a roof, for example.
[0141] Description of Reference Numerals
[0142] 1 substrate
[0143] 2 1st electrode
[0144] 3 Electron transport layer
[0145] 4 Light absorption layer
[0146] 5. Hole Transport Layer
[0147] 6. Second electrode
[0148] 7 Porous layer
[0149] 100, 200 Solar cells
Claims
1. A solar cell comprising a first electrode, a second electrode, a light absorbing layer located between the first electrode and the second electrode, and an electron transport layer located between the first electrode and the light absorbing layer, wherein: At least one electrode selected from the first electrode and the second electrode has light-transmitting property, The light absorbing layer contains a perovskite compound represented by the chemical formula ASnX3, wherein A is at least one monovalent cation selected from the group consisting of methylammonium cation, formamidinium cation, phenethylammonium cation, guanidinium cation and cesium cation, and X is a halogen anion. The electron transport layer contains an electron transport material containing Ti and Zn, wherein the electron transport material has a chemical formula of Ti x Zn 1- x O 1+x The oxide formation represented by The difference between the conduction band bottom energy level of the electron transport material and the conduction band bottom energy level of the perovskite compound is less than 0.42 eV.
2. The solar cell according to claim 1, The bottom energy level of the conduction band of the electron transport material is greater than -3.89 eV and less than -3.05 eV based on the vacuum energy level.
3. The solar cell according to claim 2, The conduction band bottom energy level of the electron transport material is greater than -3.46 eV and less than -3.24 eV based on the vacuum energy level.
4. The solar cell according to claim 1, The value of x is greater than or equal to 0.20 and less than or equal to 0.
73.
5. The solar cell according to any one of claims 1 to 4, The electron transport layer is in contact with the light absorbing layer, and The electron transport material is provided on a surface of the electron transport layer in contact with the light absorption layer.
6. The solar cell according to any one of claims 1 to 4, The invention further includes a hole transport layer located between the second electrode and the light absorbing layer.
Citation Information
Patent Citations
Photoelectric conversion device
JP2011066206A
Photoelectric conversion device and manufacturing method of the same
JP2017168499A